Parent readiness for discharge from a tertiary care pediatric cardiology unit. Issue 3 (4th July 2016) - Schuh, Michelle; Schendel, Sheena; Islam, Sunjidatul; Klassen, Keltie; Morrison, Lisa; Rankin, Kathryn N.; Robert, Cheri; Mackie, Andrew S.
Abstract: Purpose: This study aimed to measure parents' readiness for discharge from a pediatric cardiology/cardiac surgical inpatient unit. Design and Methods: An observational study was conducted at a single tertiary care pediatric cardiac surgical program; parents received teaching from a discharge coordinator, bedside nurse, and, if needed, dietician and pharmacist. We surveyed parents/guardians on the day of discharge and 2 weeks later. Results: We enrolled 181 participants, 53% with children <12 months of age. Length of hospital admission ranged from ≤7 days (54%) to >4 weeks (8%). The most common diagnoses were ventricular septal defect ( n = 39), atrial septal defect ( n = 28), and coarctation of the aorta ( n = 20). Home enteral feeding was required for 21 (12%) children, and 167 (92%) were discharged on medications. Nearly all parents ( n = 173, 96%) felt they were ready to take their child home as planned. With respect to medical needs, problems to watch for, who and when to call, what their child was allowed and not allowed to do, and knowledge about follow‐up, >90% of respondents rated their knowledge 8+ (range 0–10). Only 68% of respondents rated their knowledge ≥8 regarding services available in their community. Twenty percent experienced challenges at home for which they felt unprepared. These included infection, pain, and gastrointestinal concerns. Practical Implications: Most parents felt ready for discharge following multidisciplinary teaching. Greater emphasis is needed on teaching families about services available in the community. Further study is required to determine which parents need additional support and education to avoid unanticipated challenges post discharge.